2014
DOI: 10.1111/wej.12100
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the impact of land cover changes on water balance components of White Volta Basin in West Africa

Abstract: Land use and land cover (LULC) have been and still changing, through human activities, creating variability in hydrological cycle. This paper investigates the hydrological impacts of LULC changes on water balance in the White Volta Basin located in the West of Africa using the Soil and Water Assessment Tool (SWAT). Two LULC data for 1990 and 2006 and two plausible scenarios of land use change were evaluated. Results show a link between land cover and the hydrologic response with a decrease in land cover corres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 14 publications
3
39
0
Order By: Relevance
“…Therefore, the effects of LULC on these processes could be represented inadequately. However, the SWIM model showed in this study, like SWAT model in other LULC studies in the region [33], that the process-based models are generally able to reproduce the effects of LULC.…”
Section: Discussion Of the Methodological Framework Employed And Relamentioning
confidence: 47%
See 2 more Smart Citations
“…Therefore, the effects of LULC on these processes could be represented inadequately. However, the SWIM model showed in this study, like SWAT model in other LULC studies in the region [33], that the process-based models are generally able to reproduce the effects of LULC.…”
Section: Discussion Of the Methodological Framework Employed And Relamentioning
confidence: 47%
“…The parameter settings of the newest version of the SWAT model are used for the aggregated vegetation types of the SWIM model [32]. These parameter settings have been widely used in the African context for LULC studies (e.g., [33][34][35][36]). The effects of the vegetation on the hydrological processes include the cover-specific retention coefficient, impacting surface runoff and influencing the amount of transpiration.…”
Section: Ecohydrological Model and Model Set-upmentioning
confidence: 99%
See 1 more Smart Citation
“…Tong and Chen (2002), studying the contribution of pollutants from different types of land use, found that agricultural land use produced the highest and bare land use the least amount of contaminants. Awotwi et al (2015) found that human activity is one of the major driving forces leading to changes in land cover characteristics and subsequently hydrologic processes. Wang (2001) found that industrial land and agricultural land decrease water environment quality and forest land and grassland have a negative influence on water pollutant concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding to the impacts of land cover changes on water and soil erosion-sediment yields, most of the previous studies were conducted by hydrological modelling (Notebaert et al 2011;De Girolamo and Lo Porto 2012;Isik et al 2013;Wang et al 2014;Awotwi et al 2015). In addition, most of those studies focussed only on the impact of clear cutting in forest harvesting on water yield and soil erosionsedimentation.…”
Section: Introductionmentioning
confidence: 99%